HOSPITAL REVENUE MANAGEMENT MODEL BASED ON HUMAN CENTRED DESIGN: A CASE STUDY OF A HOSPITAL IN GHANA - Daniel Amoah (PT. ZILLZELL MEDIA PRIMA, 2025)
This study aims to enhance revenue mobilisation at Breman Seventh Day Adventist (SDA) Hospital, Kumasi, through Human-Centred Design principles and design thinking methodologies. The study employs innovation and user-centred systems theory, systems thinking theory, and service design theory. Employing a qualitative case study approach, the research sampled 24 stakeholders comprising finance staff, clinical personnel, and patients at the hospital. Data collection utilised structured interviews, focus group discussions, and observations. The study employs thematic analysis to examine patterns and generate insights. Findings revealed that revenue challenges stem from systemic integration gaps rather than isolated technical failures. This manifests through disconnected workflows, inadequate patient communication systems, and limited interdepartmental collaboration. The design thinking process successfully engaged stakeholders in collaborative problem-solving, generating innovative solutions that address multiple system components simultaneously. Findings validate the study’s theoretical background. Key recommendations include developing patient financial education programs, implementing simplified billing systems, integrating financial counselling into clinical workflows, and enhancing mobile payment options. The research demonstrates that Human-Centred Design principles effectively address complex healthcare management challenges, aligning with organisational missions and stakeholder needs. The study contributes practical frameworks for implementing participatory improvement initiatives in resource-constrained healthcare settings and provides evidence for the effectiveness of stakeholder-centred approaches to financial sustainability.